(untitled) (Journal of Hama University, 2021)
The pregnant woman coming to childbirth faces many fears regarding her pregnancy, birth and the safety of her child, which may cause her childbirth anxiety, which is characterized by many psychological and physical symptoms that may affect the outcome of pregnancy and childbirth, Therefore, our present descriptive study aimed to identify the level of childbirth anxiety among 100 pregnant women in the third trimester of pregnancy who were selected using the convenient sample method from the alshaheed Majd Abdullah Hospital and the Raml and Hasan Health Centers in Tartous Governorate. Data was collected using a pre-established birth anxiety scale. The results showed that 74% of women feel fear for the life and safety of the fetus during childbirth, 55% fear the birth of a deformed child, 38% suffer from difficulty breathing, and 30% suffer from nausea, dizziness and headache. The overall level of childbirth anxiety among women was moderate in 74% of them, as was moderate in the psychological and physical dimensions in 59% and 45% of women, respectively. The study recommended conducting educational courses for mothers who are coming to childbirth to provide them with sufficient information about pregnancy and childbirth, conducting educational and training courses for nursing staff in health centers and hospitals on identifying symptoms and signs of childbirth anxiety in pregnant women, and the best ways to deal with them, in addition to conducting more studies on factors Influencing childbirth anxiety and its relationship to quality of life for pregnant women